Area-wide urban traffic control: A Bee Colony Optimization approach. (April 2017) - Jovanović, Aleksandar; Nikolić, Miloš; Teodorović, Dušan
Highlights: We considered the Area-wide urban traffic control problem. For this problem we developed control system based on the Bee Colony Optimization. Numerical experiments were performed on well-known traffic network. Obtained results were compared with the results obtained by Simulated Annealing (SA) metaheuristic. It has been shown that the proposed BCO approach outperforms the SA algorithm. Abstract: The paper describes a new method of optimizing traffic signal settings. The area-wide urban traffic control system developed in the paper is based on the Bee Colony Optimization (BCO) technique. The BCO method is based on the principles of the collective intelligence applied by the honeybees during the nectar collecting process. The optimal (or near-optimal) values of cycle length, offsets, and splits are discovered by minimizing the total travel time of all network users travelling through signalized intersections. The set of numerical experiments is performed on well-known traffic benchmark network. The results obtained by the BCO approach are compared with the results found by Simulated Annealing (SA). It has been shown that the suggested BCO approach outperformed the SA.